Bayesian estimation of Cox model with non-nested random effects: an application to the ratification of ILO conventions by developing countries - Guillaume Horney; Bernhard Boockmann; Dragana Djurdjevic; François Laisney (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
We use a multivariate hazard model for the analysis of data on the timing of ratifications of different conventions. The model accounts for two random effects, one at the country level and the other at the convention level. We use a semi-parametric Bayesian approach, based on the partial likelihood. Our findings confirm the results of preceding studies that ratification behaviour varies substantially across members states and conventions. Furthermore, the results yield insights on the impact of unobserved heterogeneity on the ratification process.
Keywords: D78; C41; O19; C15; J80; C14; C11; 330; gibbs sampling; partial likelihood; frailties; duration analysis; Internationale Sozialstandards; Abstimmung; Statistische Bestandsanalyse; Public Choice; Schätzung; Zeit; Entwicklungsländer; Ratification